Implementation of Learning Arabic Language to Improve the Reading of the Qur'an - Jumhur Jumhur (UIN Sunan Gunung Djati Bandung, 2023)
This paper discusses the techniques, goals, and urgency of learning Arabic in improving understanding of the Qur'an. This research is library research, using qualitative data. The literature data in this study is of a secondary nature which is then written qualitatively regarding Arabic language learning and its impact on reading and writing comprehension of the Qur'an. After obtaining the data from the literature, then analyzed using a descriptive-analytical approach. This research found that those who are proficient in Arabic must memorize mufradat and learn the sciences of uthala'ah, muhadatsah, insya', Nahwu and Sharaf. Understanding of these various sciences will also lead someone to four skills; First, listening skills, namely language skills that are receptive, receiving information from other people. Second, meaningful reading skills understand changes in the form of writing into a form of meaning. Third, writing skills, namely language skills that produce or provide information to other people (readers) in written form. Writing is a change in the form of thoughts or feelings into a form of writing. Fourth, speaking skills. In addition, it was also found that the urgency of learning Arabic on the Koran is to preserve the purity of the Koran, understand the contents of the Koran, and eradicate al-Qur'an illiteracy.